2014
DOI: 10.3389/fnagi.2014.00313
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Beta1–42 and the Phoshorylated Tau Threonine 231 in Brains of Aged Cynomolgus Monkeys (Macaca fascicularis)

Abstract: Pathological hallmarks indicative of Alzheimer’s disease (AD), which are the plaques of amyloid beta1–42 and neurofibrillary tangles, were found in brain of aged cynomolgus monkey. The aim of this study was to investigate if aged monkeys exhibiting spatial memory impairment and levels of biomarkers indicative of AD, had brain lesions similar to human patients suffering from senile dementia. Generating immunohistochemistry technique to biomarkers of amyloid beta1–42 and the phosphorylated tau 231, our study ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 43 publications
1
40
1
Order By: Relevance
“…Monkeys have identical Aβ amino acid sequence to humans (Selkoe et al, 1987), which may result in similar mechanisms for Aβ production and accumulation. It has widely been reported that aged non-human primates present amyloid accumulation in the form of diffuse and compact plaques, mainly in the cortex (Cork et al, 1990; Gearing et al, 1996, 1997; Giannakopoulos et al, 1997; Kimura et al, 2003; Bons et al, 2006; Lemere et al, 2008; Oikawa et al, 2010; Perez et al, 2013; Sridharan et al, 2013; Darusman et al, 2014). Amyloid plaques in the cortex of old marmoset have been previously described as well (Maclean et al, 2000; Geula et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monkeys have identical Aβ amino acid sequence to humans (Selkoe et al, 1987), which may result in similar mechanisms for Aβ production and accumulation. It has widely been reported that aged non-human primates present amyloid accumulation in the form of diffuse and compact plaques, mainly in the cortex (Cork et al, 1990; Gearing et al, 1996, 1997; Giannakopoulos et al, 1997; Kimura et al, 2003; Bons et al, 2006; Lemere et al, 2008; Oikawa et al, 2010; Perez et al, 2013; Sridharan et al, 2013; Darusman et al, 2014). Amyloid plaques in the cortex of old marmoset have been previously described as well (Maclean et al, 2000; Geula et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…NFTs cause neuronal dysfunction and eventually lead to death (Avila et al, 2006; Stokin and Goldstein, 2006). In several aged non-human primates, hyperphosphorylated tau filaments have been observed in hippocampus and cortex of old subjects (Härtig et al, 2000; Schultz et al, 2000a,b; Oikawa et al, 2010; Perez et al, 2013; Darusman et al, 2014). To our knowledge, there are no previous reports of hyperphosphorylated tau in marmosets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Aβ 42 and Aβ 40 , two major Aβ isoforms, Aβ 42 is more insoluble and prone to aggregation (Miners et al 2014). The insoluble Aβ 42 progressively increases with age and further aggravates in the AD brain, which is accompanied with cognitive decline (Darusman et al 2014;Fukumoto et al 2004;Yue et al 2014). Increasing evidence has shown that Aβ oligomers trigger neurotoxicity, probably via phosphorylated tau (p-tau) (Selenica et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data indicate aging related neuropathologies like those observed in human AD also occur, suggesting that macaques may be promising models of sporadic AD [24,25]. Cynomolgus macaques ( Macaca fascicularis ), in particular, accumulate age-related cognitive deficits, brain amyloid, and tauopathies [26,27]. Age-related cognitive impairment has been associated with altered cerebrospinal fluid (CSF) biomarkers of AD-like pathology, including decreased beta-amyloid 1-42 and increased total and phosphorylated tau [28].…”
Section: Introductionmentioning
confidence: 99%